Enhancing global competitiveness of penang electronics and electrical small and medium industries through improving linkage programmes - Lee, Huay Kuan (2006)
Penang has positioned itself to become one of the most industrialized states in Malaysia, and has taken up the challenge of achieving Vision 2020. Due to the present economic slowdown, it is timely to carry out a research on the formulation of an innovative linkage programmes and improvement strategies for SMIs in Penangâ€™s electronics and electrical manufacturing industry in facing the global competition. The next phase of industrialization strategy needs to be more innovative, given the new challenges and opportunities at both domestic and international levels. The government and MNCs should continue to ensure a liberal and conducive investment climate and emphasize the role of SMIs to support the industrial development in Penang. The innovative linkage programme need to base on the â€œPartners in Developmentâ€? principle, whereby the SMIs, MNCs and the government work together as a team. The rationale of the linkage programme is to increase productivity and international competitiveness towards further improving the economic growth of Penang. In order to attain a 100 percent on data return, face-to-face interviews or personal delivery of the survey questionnaire were carried out on 115 respondents from two difference groups, i.e. SMIs and MNCs whose activities are related to electronics and electrical manufacturing industry in Penang. The research finding enables SMIs to get the most benefit from the presence of the MNCs, with the strong support from the state government. There are two prong aspects of this research : firstly to understand specifically the extent of those innovative programmes; secondly the identification of strategies to improve the programmes or to remove the obstacles to potential programme. No doubt, after the implementation of these programmes and strategies, together with the combined efforts from MNCs and government, Penang SMIs will be more competitive